Foreign Direct Investment, Institutional and Environmental Quality: An Empirical Analysis of the Sub-Saharan African Region - Benhrouz, Mohamed Ghofrane; Smaali, Taha; Hidri, Sabrina; Mensi, Sami (Journal of Ecohumanism, 2025)
This paper examines the impact of foreign direct investment (FDI), trade openness, institutional quality, and other independent variables on environmental quality in 37 sub-Saharan African countries observed between 2012 and 2021. The results reveal that trade openness relates to a decrease in carbon emissions, while FDI has a negative effect on these emissions. The study highlights the importance of institutions, recommending countries to focus on improving rule of law and political stability to achieve a higher environment quality. Furthermore, promoting renewable energy consumption is recommended. These conclusions suggest that trade-friendly policies, foreign direct investment (FDI), and institutional reforms are prerequisites to guide countries towards sustainable development and an improvement in environment quality.